2014
DOI: 10.1016/j.rbmo.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Italian Constitutional Court removes the prohibition on gamete donation in Italy

Abstract: In 2004, The Italian Constitutional Court prohibited treatments involving gamate donation, embryo donation, embryo cryopreservation (except under exceptional circumstances), and the transfer of more than three embryos. Basically three statements were made by the Court: the ban violates a couple's fundamental right to health, to self-determination and to have a child. Here, the consequences of such a decision and the legal challenges that ensued are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
(7 reference statements)
0
14
0
1
Order By: Relevance
“…Law 40 was to have immediate catastrophic effects on assisted reproduction techniques in Italy. Mean pregnancy rate per transfer declined and the rate of multiple pregnancies increased (Benagiano et al, 2014). Overnight, there was an exodus of Italian fertility patients looking for appropriate treatments overseas.…”
Section: Reversal Of Law 40 In Italymentioning
confidence: 99%
See 3 more Smart Citations
“…Law 40 was to have immediate catastrophic effects on assisted reproduction techniques in Italy. Mean pregnancy rate per transfer declined and the rate of multiple pregnancies increased (Benagiano et al, 2014). Overnight, there was an exodus of Italian fertility patients looking for appropriate treatments overseas.…”
Section: Reversal Of Law 40 In Italymentioning
confidence: 99%
“…Indeed, in 2012, the European Court of Human Rights ruled that Italy's ban on embryo screening [by PGD] breached two articles of the European Convention of Human Rights, including the right to respect for family and private life. The ruling followed the challenge of an Italian couple whose first child had died from cystic fibrosis (Benagiano et al, 2014).…”
Section: Reversal Of Law 40 In Italymentioning
confidence: 99%
See 2 more Smart Citations
“…During the period when Italian law required all embryos created in a fresh cycle to be transferred and embryo cryopreservation was not allowed (Benagiano et al, 2014), there was intense pressure to improve the pregnancy rates from the supernumerary oocytes that could neither be fertilised nor transferred. These frozen-thawed oocytes made a valuable contribution to the cumulative pregnancy rate in Italy and demonstrated that "stopping the biological clock" for older would-be mothers could give them the opportunity of healthy pregnancies at an advanced age.…”
mentioning
confidence: 99%